Spectral and Spatial Analysis of Plantar Force Distributions Across Foot-Strike Patterns During Treadmill Running - Paul William Macdermid; Stephanie Julie Walker (Applied Sciences)
Treadmill running gait differs to overland running and is commonly used to evaluate interventions. One challenge is accurately defining strike pattern and related impact kinetics. This study aimed to characterise foot-strike patterns during treadmill running using the spatial distribution of in-shoe plantar forces and to identify differences in impact kinetics through spectral analysis. Low- and high-frequency power components were analysed in heel, midfoot and forefoot strike patterns. No distinct impact peaks were identified in the force traces; however, significant spatial differences were found. Forefoot strikes exhibited lower peak impact force, average loading rate, and high-frequency power spectral density (PSD) components compared to heel and midfoot strikes, with heel also lower than midfoot. Strike pattern classification was derived from spatial force distribution, where >70% posterior and >50% anterior denote heel and forefoot strikes, while midfoot strikes demonstrate a more balanced distribution with >25% in the central zone. These findings support the integration of spatial, force-based classification with frequency-domain analysis to enhance the evaluation of impact attenuation in treadmill-based running interventions.